Evaluation of Land Suitability for Patchouli Plants in Pantai Tinjau Village, Sekerak District, Aceh Tamiang Regency - Salsabila; Mulyani, Cut; Iswahyudi (Journal Galung Tropika, 2025)
Patchouli (Pogostemon cablin Benth) is one type of industrial plant that has the potential to be developed as one of the superior regional commodities in Aceh Tamiang district, which has so far only focused on oil palm and rubber plants. The study aimed to determine the suitability of patchouli land in Pantai Tinjau Village, Sekerak District, Aceh Tamiang Regency. The study used a survey method with descriptive analysis based on field observations and laboratory analysis with sample determination by "purposive sampling." The data used were primary and secondary data and results of field observations. The parameters observed were the physical and morphological properties of the land where, among others, soil type, adequate depth, field texture, soil structure, surface drainage, flooding/puddles, rocks on the surface, rock outcrops, slope degree, management level, altitude. The observed soil chemical properties parameters were pH, C-Organic, N-Total, P-Total, K-Total, P-Available, Exchangeable cations-anions, CEC, base saturation, and salinity. Soil sampling in the land unit area based on soil maps by drilling. The selected points represent each Pahan Map Unit (SPL) consisting of 3 SPLs, and 3 soil samples were taken at each SPL. The evaluation results showed that the growth of patchouli plants in Pantai Tinjau Village was hampered by several main limiting factors, namely rooting media, nutrient retention and availability, and the level of erosion hazard. Although some land can be improved in suitability class through improvement, several obstacles such as soil texture and slope remain difficult to overcome.